Milk production of rabbit doe and kit mortality as affected by dietary katuk leaf meal (Sauropus androgynus L. Merr) - Akbar, Mubarak; o, Sjofjan; s, Minarti (Indonesian Journal of Animal and Veterinary Sciences, 2013)
This study was aimed as to determining the effect of katuk (Sauropus androgynus L. Merr) leaf on influence rabbit doe milk production and kits mortality during 3 weeks weeks of age. Twenty four does aged 6-12 months, divided into three blocks, of four treatment diets, were used in our replicity. The diet treatments used katuk leaf meal: 0% (P0), 1% (P1), 2% (P2), and 3% (P3). The parameters observed were: doeâs milk production, kits mortality, kit as level: body weight gain, and immune response. The results showed that supplementation of katuk leaf meal increased (P < 0,05) doe milk production and body weight gain of kits during 3 weeks experiment, whereas mortality and immune responses were not affected by katuk leaf meal supplementation. Key Words: Katuk Leaf Meal, Rabbit Does Milk Production, Kit Mortality